Detective knight, Independence [videorecording (DVD)] - Drake, Edward; Large, Corey; Willis, Bruce, 1955-; Kilmer, Jack, 1995-; Munro, Lochlyn, 1966- (Lionsgate, 2023)
Detective James Knight is in this final, tense chapter of the trilogy. Knight's last-minute assignment to the Independence day shift turns into a race to stop an unbalanced ambulance EMT from imperiling the city's festivities. The misguided vigilante, playing a cop with a stolen gun and uniform, has a bank vault full of reasons to put on his own fireworks show'one that will strike dangerously close to Knight's home.